2002
DOI: 10.1046/j.0022-3042.2001.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential induction of embryonic and adult forms of glutamic acid decarboxylase during in vitro‐induced neurogenesis in cloned neuroectodermal cell‐line, NE‐7C2

Abstract: The expression of different forms of glutamate decarboxylases and GABA was investigated in the course of retinoic acid-induced neuronal differentiation of NE-7C2 cell-line established from brain vesicles of 9-day-old mouse embryos lacking functional p53 gene. Non-induced NE-7C2 cells expressed embryonic GAD mRNAs with a low level of embryonic GAD25 protein and did not contain detectable amounts of GABA. Addition of 10 )6 M retinoic acid induced the expression of N-tubulin and a significant increase in the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…For amplification of different GAD transcripts, we used PCR primerpairs specific for embryonic GADs and GAD65, as described previously (Varju et al, 2002). Adult GAD67 amplification was performed using a forward primer spanning the exon 6 -8 border region (Table 1), thus precluding amplification of exon 7A/B-containing embryonic cDNAs.…”
Section: Sequential Expression Of Gad Mrnas In the Developing Lensmentioning
confidence: 99%
See 3 more Smart Citations
“…For amplification of different GAD transcripts, we used PCR primerpairs specific for embryonic GADs and GAD65, as described previously (Varju et al, 2002). Adult GAD67 amplification was performed using a forward primer spanning the exon 6 -8 border region (Table 1), thus precluding amplification of exon 7A/B-containing embryonic cDNAs.…”
Section: Sequential Expression Of Gad Mrnas In the Developing Lensmentioning
confidence: 99%
“…EGAD (GAD25 and GAD44) showed a transient temporal expression pattern similar to that characteristic for the embryonic nervous system (Szabo et al, 1994): it was low at the earliest stages (E15.5); peaked at E17.5, the stage of most intensive primary fiber cell terminal differentiation (Kaufman, 1992); gradually decreased until a The positions are relative to the ATG codons of the corresponding cDNAs. Primers for actin, EGAD, and GAD65 were as published in Varju et al (2002). RT-PCR, reverse transcriptase-polymerase chain reaction; F, forward; R, reverse primers; GAD, glutamic acid decarboxylase.…”
Section: Temporal Regulation Of Gad Proteins and Gaba In The Developimentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas cell lines can also be manipulated to over-express GAD65 Thompson et al 2000), little has been reported regarding inherent GAD65 expression or putative GABAergic function for immortalized cell lines during neuronal differentiation. Promoter studies have been performed in the P19 embryonic carcinoma line (Pinal et al 1997), and GAD65 expression has been reported in human fibroblasts and in neuroectodermal and insulinoma cell lines (Kono et al 2001;Salazar et al 2001;Varju et al 2002). The neuronal cell line NTera-2N is negative for GAD65 mRNA (Yoshioka et al 1997), and although PC12 cells have been found to modulate GAD65 and GAD67 expression in response to hypoxia, they are not otherwise GABAergic (Kobayashi and Millhorn 2001).…”
Section: Introductionmentioning
confidence: 97%